2016
DOI: 10.1039/c6nr01896c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high aspect ratio nanogrid transparent electrodes via capillary assembly of Ag nanoparticles

Abstract: In this report, we describe the fabrication of periodic Ag nanogrid electrodes by capillary assembly of silver nanoparticles (AgNPs) along patterned nanogrid templates. By assembling the AgNPs into these high-aspect-ratio nanogrid patterns, we can obtain high-aspect-ratio nanogratings, which can overcome the inherent trade-off between the optical transmittance and the sheet resistance of transparent electrodes. The junction resistance between the AgNPs is effectively reduced by photochemical welding and post-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Sciacca et al [87] fabricated patterned Ag electrodes, which showed a higher conductivity than thermally evaporated networks. Another approach to fabricate Ag nanogrids from solution was presented by Kang et al [89] , who deposited Ag nanoparticles into nanogrid templates via capillary assembly. The obtained electrodes displayed a sheet resistance of 15 Ohm sq -1 and an optical transmittance of 85 % (FoM=148).…”
Section: Metal Gridsmentioning
confidence: 99%
“…Sciacca et al [87] fabricated patterned Ag electrodes, which showed a higher conductivity than thermally evaporated networks. Another approach to fabricate Ag nanogrids from solution was presented by Kang et al [89] , who deposited Ag nanoparticles into nanogrid templates via capillary assembly. The obtained electrodes displayed a sheet resistance of 15 Ohm sq -1 and an optical transmittance of 85 % (FoM=148).…”
Section: Metal Gridsmentioning
confidence: 99%
“…[40][41][42] However, due to the poor conductivity between individual particles, they are usually required to deposit on the substrates with transparent grids/ meshes via solution-based printing techniques for TEs applications. [43,44] Recent report on one-step sintered AgNPs thin film by chemical treatment indicate its potential as TEs. [45] However, the sheet resistance of ultrathin connected Ag nanoparticles (AgNPs) film is large (150 Ω sq −1 ) when AVT over 60% in visible region.…”
Section: Introductionmentioning
confidence: 99%
“…Metal NPs or NWs can be used as the building block to fill in the valley of the polymer template. After proper welding process to reduce the contact resistance between each building block, the metal NPs or NWs will be integrated for the formation of metal mesh . The patterned polymer template can also be fabricated on a conductive substrate, which allows the electrodeposition of metal mesh in the valley with the conductive layer directly exposed to the electrolyte .…”
Section: The Front Metal Electrodementioning
confidence: 99%